2019
DOI: 10.1186/s12931-019-0996-z
|View full text |Cite
|
Sign up to set email alerts
|

Second-hand smoke exposure in adulthood and lower respiratory health during 20 year follow up in the European Community Respiratory Health Survey

Abstract: Background Early life exposure to tobacco smoke has been extensively studied but the role of second-hand smoke (SHS) for new-onset respiratory symptoms and lung function decline in adulthood has not been widely investigated in longitudinal studies. Our aim is to investigate the associations of exposure to SHS in adults with respiratory symptoms, respiratory conditions and lung function over 20 years. Methods We used information from 3011 adults from 26 centres in 12 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…In the present study, the prevalence of subjects exposed to ETS in 2012 was 5%, which is consistent with another European study [17]. With the reduction in smoking prevalence and policies to restrict smoking in public places ETS exposure has been decreasing both in Europe and in the United States [17,25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the prevalence of subjects exposed to ETS in 2012 was 5%, which is consistent with another European study [17]. With the reduction in smoking prevalence and policies to restrict smoking in public places ETS exposure has been decreasing both in Europe and in the United States [17,25].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the prevalence of subjects exposed to ETS in 2012 was 5%, which is consistent with another European study [17]. With the reduction in smoking prevalence and policies to restrict smoking in public places ETS exposure has been decreasing both in Europe and in the United States [17,25]. In Finland, the first law to restrict smoking was put into operation in 1977 [26], and since the 1980s' ETS exposure has decreased significantly [5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…29 Similarly, a recent study from the ECRHS found associations between SHS exposure and physician-diagnosed asthma and poorer asthma control in adults, yet no effect was observed on the lung function. 30…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…This is the combination of two phenomena: Second-Hand Smoke (SHS) and Third-Hand Smoke (THS) [6]. ETS is an issue of great public health concern because it has been linked with a large number of pathologies, including cardiovascular, respiratory and neoplastic ones [7][8][9]. In addition to the worsening of indoor air quality, scientific evidence demonstrated that smoking may also be considered a source of outdoor pollution, since it produces pollutants which can contaminate outdoor air and persist for a long time [10][11][12].…”
Section: Introductionmentioning
confidence: 99%